PENGEMBANGAN MULTIMEDIA INTERAKTIF PEMBELAJARAN DESAIN PANEL - Nirmala Wahyuni; Marlina Marlina (Fesyen Perspektif, 2017)
Learning panel design is still done conventionally. Media used in the delivery of material in the form of visual media infokus. Based on the current learning media continue to be developed one through the development of interactive multimedia instructional design panel. The research objective is to develop interactive multimedia learning design manufacture panels using Adobe Photoshop. The proper method for this study is the method of approach R D (Research and Development). This study was conducted in Education Studies Program dressmaking Family Welfare Department of Education Faculty of Technical Education and Vocational Education University of Indonesia. The study population is learning materials expert panel design, multimedia experts and students of Education Studies Program dressmaking which had followed the panel design learning course on Design Technology as a partner for the enrichment and validation. Results of the validation by experts of material to get an average value of 97.18% percentage feasibility, by multimedia experts earn an average percentage of 95.05% eligibility by the user and get an average percentage of 95.31% worthiness. The tests concluded based on a standard feasibility of developing interactive multimedia instructional design manufacture panels to fall into the category fit for use.